Word-Displacement in The Poetry of Alsa’aleek “Vagabonds” (Selected Examples) - Maitham Raheem Shaghati ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Literary phenomena are characterized by a kind of word-displacement in depicting reality in different ways based on what the poet creates with his broad imagination. It produces a pattern of astonishing strangeness and an amazement has a strong effect on standardizing how a recipient conveys the text. It was a live representation of this reality, and a true reflection of the atmosphere in which it derived its strength and meaning. Scholars still do not pay the attention to the literary phenomena, with their different characteristics in various fields of Arabic disciplines especially in word-displacement in the old and modern poetry since it has an effective strength. It obligates to identify the productive requirements of the poetic discourse since it was a notion that resulted from the events that affected the poet’s spirit. It made him or her to write his or her poetry according to their requirements. One of the most prominent literary phenomena is word-displacement, which surged in the post-modern era where it became common in the curricula, syllabuses, and literary schools that work to read the poetic text according to well-known mechanisms and steps of standardized procedures. It became very common. Most critics began to achieve their goal from readings of poetic discourse based on the mechanisms of this phenomenon. The theory of word-displacement received an attention and the current study focused on what the researcher had prepared of its importance by paying attention to its stylistic, pictorial, and linguistic levels